1997
DOI: 10.2527/1997.75123353x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amount of whole barley, barley bulk density, and form of roughage on feedlot lamb performance, carcass characteristics, and digesta kinetics.

Abstract: We conducted two feedlot trials and one metabolism trial to evaluate the effect of barley level, barley bulk density, and physical form of roughage on lamb growth performance and digesta kinetics. Level of whole barley (50, 70, 90%) and type of roughage (chopped or pelleted alfalfa) were evaluated in Trial 1 (50 d period). Trial 2 (50 d) evaluated barley bulk density (heavy = 671 and light = 607 kg/m3), form of roughage (pelleted or chopped alfalfa), and level of barley (80 or 40%). The influence of treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
2
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
5
2
0
2
Order By: Relevance
“…Increasing the level of barley in the diet resulted in a linear increase (P < 0.05) in total VFA levels at 1000 and 1400 h (Table 3). Our results are consistent with other studies which showed reduced ruminal pH and increased total VFA levels as the amount of rapidly fermented carbohydrate from barley grain in the diet increased (McAllister et al 1990;Feng et al 1995;Hatfield et al 1997).…”
Section: Metabolism Trialsupporting
confidence: 93%
See 2 more Smart Citations
“…Increasing the level of barley in the diet resulted in a linear increase (P < 0.05) in total VFA levels at 1000 and 1400 h (Table 3). Our results are consistent with other studies which showed reduced ruminal pH and increased total VFA levels as the amount of rapidly fermented carbohydrate from barley grain in the diet increased (McAllister et al 1990;Feng et al 1995;Hatfield et al 1997).…”
Section: Metabolism Trialsupporting
confidence: 93%
“…This resulted in a lower (P < 0.05) acetate:propionate ratio for the barleybased diets. These results are in agreement with other researchers who reported similar responses for molar proportions of ruminal acetate and propionate to increased levels of readily fermentable carbohydrates in the diet (Hatfield et al 1997;Reinhardt et al 1997). The observed changes in molar ratios of acetate:propionate are related to a decline in ruminal pH after feeding to or below 5.5, as a result of bar- For personal use only.…”
Section: Metabolism Trialsupporting
confidence: 93%
See 1 more Smart Citation
“…Os autores sugerem que os cordeiros que receberam ração no sistema livre escolha ingeriram menos concentrado, resultando em menor acidose. HATFIELD et al (1997), ao compararem alfafa peletizada e moída, não verificaram diferenças no desempenho dos cordeiros, porém aqueles que receberam alfafa moída apresentaram maior taxa de amido fecal.…”
Section: Johnston (1992) Observou Que Os Cordeiros Criados Em Creep Funclassified
“…Assim, a suplementação dos cordeiros lactentes afirma-se como uma prática de manejo prioritária e estratégica na produção de cordeiros, devendo ser iniciada logo após o nascimento, com a finalidade de adaptar os animais ao consumo de alimento sólido. Além disso, a qualidade da fibra torna-se um fator importante na dieta, tendo em vista que os cordeiros são mais suscetíveis à acidose aguda, quando comparados aos bovinos (HATFIELD et al, 1997).…”
Section: Rev Bras Zootec 30(3):941-947 2001 (Suplemento 1) Introunclassified